Harnessing the therapeutic value of Tanshinone IIA: a breakthrough therapy in cardiovascular diseases - Lanxiang Du; Chengyan Guan; Hao Zhang; Haoyue Jia; Qiang Wan; Qiang Wan (Frontiers in Pharmacology, 2025)
Cardiovascular diseases (CVDs) have emerged as one of the leading causes of global mortality and health burden, with their prevalence and mortality rates demonstrating a persistent upward trend, thereby posing significant challenges to public health worldwide. Tanshinone IIA (Tan IIA), the principal lipophilic bioactive component isolated from Salvia miltiorrhiza Bunge, has gained substantial recognition in cardiovascular therapeutics. Accumulating evidence from recent investigations has demonstrated that Tan IIA exhibits multi-target pharmacological properties and modulates diverse signaling pathways in cardiovascular protection, positioning it as a promising candidate in natural product-based drug discovery. The therapeutic efficacy is mediated through multiple mechanisms, including but not limited to anti-atherosclerotic effects, lipid homeostasis regulation, anti-arrhythmic properties, myocardial functional enhancement, and hemodynamic stabilization. This comprehensive review systematically elucidates the molecular mechanisms and therapeutic targets underlying Tan IIA’s cardio-protective effects, particularly focusing on its anti-inflammatory, antioxidant, anti-atherosclerotic, and myocardial preservation properties. Furthermore, we critically evaluate its current clinical applications and propose potential directions for future research to optimize its therapeutic potential in cardiovascular medicine.